Trust in interaction studies - Muntigl, Peter; Scarvaglieri, Claudio; De Wilde, July; Bührig, Kristin; Wamprechtshammer, Anna (Frontiers in Communication, 2024)
Trust is argued to be essential in fostering cooperative communication, whereas a lack of trust is seen as detrimental to these aims. Over the years, there has been a slow but steady stream of research that has aimed to shed light on how trust is accomplished or broken down through discursive-interactional practices. In this mini review, we examine existing studies that take trust as a topic of investigation using micro-analytic, interactional methods, in order to provide readers with an up-to-date overview on new developments in this important field of research. From this review, we conclude that there exist two different, yet complementary, views on trust: Trust as an interactional principle and trust as a discursively accomplished phenomenon. We not only summarize important discursive work that provides a unique lens on how trust may be established and maintained through verbal and non-verbal resources, but also suggest some of the challenges interactional trust research still faces and some important areas for further investigation in which trust is a major concern.